Examining the Experts : A Comparative Analysis of the Role of Expert Witnesses in Court Systems of the Western Balkans - World Bank Group (World Bank, Washington, DC, 2019)
This Report examines if and how expert witnesses impact the integrity, impartiality and efficiency of adjudication in four countries—Serbia, Montenegro, North Macedonia and Bosnia and Herzegovina (BiH). The report is part of a broader World Bank initiative to raise awareness of reform opportunities and inform policy dialogue on efficiency of justice, quality of justice and access to justice across countries in the Western Balkans, with a view to improving the performance of their justice systems. The Report provides an objective review of the performance of the justice system in the selected countries and recent achievements and opportunities for reform vis a vis the role of expert witnesses in trials. Recognizing the formative role that expert witnesses play in the trial process, the report provides recommendations on how to leverage and improve the role of expert witnesses in trials with a view to enhancing the overall quality, efficiency and performance of the justice system.